Status Mutu Sungai Sungai Pundul, Kutasari Kabupaten Purbalingga - Naufal Afifah; Eric Armando; Waluyo (Talenta Publisher, 2025)
The purpose of this study was to determine the condition of water quality and water pollution conditions in the Pundul River, Kutasari. The research location, namely station 1 is at coordinates -7.363170 LS and 109.335832 BT, station 2 -7.364296 LS and 109.337737 BT, station 3 -7.366209 LS and 109.338324 BT, station 4 -7.368257 LS and 109.340588 BT, and station 5 -7.369092 LS and 109.340915 BT. The data collection method used is the observation method with a quantitative approach (using the STORET and CCME-WQI methods) and qualitative (comparison of sample data with PP No.22 of 2021). The parameters used are temperature, pH, DO, COD, BOD, and total coliform. Parameters that do not meet the class III quality standards are pH with results ranging from 5.37-6.37 and total coliform with a range of 3,500 - 2,400,000 MPN / 100 ml. The data analysis used is the STORET and CCME-WQI methods. Based on the results of the pollution analysis, the Pundul River flow is in the moderately polluted category with a value of -17 and the most polluted station is at station 2 due to direct waste discharge from vermicelli noodle producers. The results of the analysis of the water quality standard status in the Pundul River flow are still in the less category with an average value of 54.14, so it is still in poor condition for tilapia fish farming activities in Kutasari District, Purbalingga.